ANALISIS PENGARUH KEMIRINGAN UPPER FACE TERHADAP KESTABILAN BLOK BAJI DI KUARI PENAMBANGAN ANDESIT SITE SOMOREJO, CV. GUNUNG MULIA, DESA SOMOREJO, KECAMATAN BAGELEN, KABUPATEN PURWOREJO, PROVINSI JAWA TENGAH - Hendra Rezkie; Singgih Saptono (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2022)
CV. Gunung Mulia is a business entity engaged in the andesite mining industry. The mining area uses an open mining system (surface mining) with the quarry mining method. There were many landslides in the research location. After performing a kinematic analysis using the stereographic method, two discontinuity areas were found in the form of major and minor joints that form wedge blocks on the mining slope. In analyzing the stability of the wedge block, one of the important parameters required is the orientation of the upper face. The method used is limit equilibrum wedge method. Based on the research result, it was found that the orientation of the angle of the slope greatly affects the value of the factor of safety. The gentler the angle of the slope, the higher the safety factor. As a recommendation, it is hoped that the upper face angle will be leveled again so that it can increase the FK value, which is at least 7° with an FK value of 5.93